Nutritional value of salad Crimean onion - N. A. Golubkina; V. I. Nemtinov; Yu. N. Kostanchuk; G. Caruso; A. F. Agafonov; I. S. Mastyaev; S. M. Nadezhkin (Овощи России, 2020)
Relevance. Allium cepa L. is considered to be one of the most important agricultural crops in most countries of the world. High nutritional value is especially pronounced in salad onion which vegetation needs high temperature and significant insulation.Material and methods. The first biochemical characteristics are given for 9 Crimean salad onion genotypes and varieties (red onions Festivalny, Yaltinsky plus, Yaltinsky foros, Yaltinsky rybin, Yaltinsky 6А, Yaltinsky 7А, Yaltinsky 8А and yellow cultivars Kendy and Bean promine) with the comparison with the appropriate data for popular Italian sweet onion cultivar Tropea and semi-pungent varieties grown in Moscow region, Italy and Stavropol region (Zolotnichok, Cherny prince).Results. Warm climate is shown to increase the amount of antioxidants, monosaccharides and organic acids in onion bulbs. Compared to the Italian Tropea variety Crimean genotypes were characterized by higher levels of ascorbic acid (12.8±1.4 mg/100 g fresh weight) and organic acids (1.58±0.03 mg malic acid per g of dry weight), relatively similar levels of polyphenols (21.0±2.3 mg-eq Gallic acid per g of dry weight), and quercetine. (3.09±0.42 mg-eq Gallic acid per g of dry weight) and antocyanines (2.78±1.03 mg/g fresh weight). New genotypes Yaltinsky 6A, Yaltinsky 7A, Yaltinsky 8A were shown to accumulate higher levels of antioxidants. A direct correlation between the peel/inner layers ratio of antioxidant activities with the appropriate ratio for polyphenols was demonstrated (r=+0.93). A direct correlation between flavonoids content in peel and inner layers was also revealed (r=+0.83). Polyphenols and flavonoids ratios between peel and inner layers were shown to be higher for the Crimean genotypes compared to semi-pungent Moscow region varieties which indicates the prospects of utilization of the Crimean onion peel in production of functional food products with elevated levels of antioxidants.